Waterfront Heirlooms: Reflections of the Kampong China Peranakan by Rosita Abdullah Lau - Ong Puay Liu; Pue Giok Hun; Loo Hong Chuang (Kajian Malaysia, 2019)
To enthusiasts of Peranakan heritage, this book Waterfront Heirlooms: Reflections of the Kampong China Peranakan, provides a window to the world of the Peranakan Chinese in a location that may surprise many – Kuala Terengganu. Imagine Terengganu, a state with more than 94% Malays, yet, in the heart of the capital city, Kuala Terengganu, a vibrant community with a distinctive culture and lifestyle survived the test of time and rapid development.